PENERAPAN MODEL LEARNING CYCLE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP ISLAM RAUDHATUL JANNAH PAYAKUMBUH TAHUN PELAJARAN 2013/2014 - Sari, Nila Madu; Rismen, Sefna; Cesaria, Anna (Pendidikan Matematika, 2013)
This research is motivated by studentâs understanding of matematical concepts. The purpose of this research is to know what is student`s understanding of matematical concepts at grade VIII SMP Islam Raudhatul Jannah Payakumbuh that use learning cycle model better than conventional model. Kind of this research is experimental research, with research plan is Randomized Â to Subject. Population of this research is student`s at grade VIII SMP Islam Raudhatul Jannah Payakumbuh academic year 2013/2014. The instrumentation of this research is understanding test of mathematical concepts. Technique of data analysis is used in this research is t-test one side by using software MINITAB. Based on the result of t-test is P-value = 0,001, it means lower than Â = 0,05, therefore hipotesis is accepted furthermove. We can conclude that student`s understanding of mathematical concepts is treated by using learning cycle better than student`s understanding of mathematical concepts is treated by using convensional learning at grade VIII SMP Islam Raudhatul Jannah Payakumbuh academic year 2013/2014.